Treatment of relapsed/refractory chronic lymphocytic leukemia/small lymphocytic lymphoma with the BTK inhibitor zanubrutinib: phase 2, single-arm, multicenter study - Wei Xu; Shenmiao Yang; Keshu Zhou; Ling Pan; Zengjun Li; Jianfeng Zhou; Sujun Gao; Daobin Zhou; Jianda Hu; Ru Feng; Haiwen Huang; Meng Ji; et al. (Journal of Hematology & Oncology, 2020)
Abstract Background Bruton tyrosine kinase (BTK) inhibitors have demonstrated a high degree of efficacy in the treatment of B cell malignancies characterized by constitutive B cell receptor activation, including chronic lymphocytic leukemia/small lymphocytic lymphoma (CLL/SLL). Methods The efficacy and safety of zanubrutinib, an investigational highly selective BTK inhibitor, was evaluated in this single-arm, phase 2 study of Chinese patients with relapsed/refractory CLL/SLL. The primary endpoint was overall response rate as assessed by an independent review committee. Results Of the 91 evaluable patients, 77 (84.6%) achieved a response, with three (3.3%), 54 (59.3%), and 20 (22%) patients achieving a complete response, partial response, and partial response with lymphocytosis, respectively, after a median follow-up of 15.1 months. The estimated 12-month event-free rate for duration of response was 92.9%. The most commonly reported grade ≥ 3 adverse events (AEs) were neutropenia (44%), thrombocytopenia (15.4%), lung infection/pneumonia (13.2%), upper respiratory tract infection (9.9%), and anemia (8.8%). The 12-month overall survival rate was 96%. Eight (9.0%) patients discontinued zanubrutinib due to AEs, and seven (8.0%) patients required at least one dose reduction. Conclusion Treatment of patients with relapsed/refractory CLL/SLL with zanubrutinib was generally well tolerated and resulted in a high overall response rate, thereby conferring a favorable benefit-risk profile. Trial registration Prospectively registered in China public registry (CTR20160890) on December 7, 2016: http://www.chinadrugtrials.org.cn/ . Retrospectively registered in ClinicalTrials.gov ( NCT03206918 ) on July 2, 2017.